“VOLTA À DITADURA”? RETORNO DA UTOPIA AUTORITÁRIA PRESENTE NAS MEMÓRIAS DE MILITARES E CIVIS DE 1964. - COSTA CARDOSO, LUCILEIDE (Universidad Nacional del Litoral, 2018)
The aim of this article is to bring back some nuanced memory aspects concerning the resentment of 1964 Brazilian military dictators, displayed in books from the 1980’s and 1990’s as a response to narratives told by leftist democratic partisans. The intention is to reflect upon a context in which Brazilian memory is object of dispute, the moment at which the victims’ narratives are no longer hegemonic or are at least weakened, and at which certain social groups express a wish for military intervention as a means to solve political and economic crisis, thus choosing new authoritarian agents as their rulers.